2021
DOI: 10.3390/cells10102586
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Permeability Transition Causes Mitochondrial Reactive Oxygen Species- and Caspase 3-Dependent Atrophy of Single Adult Mouse Skeletal Muscle Fibers

Abstract: Elevated mitochondrial reactive oxygen species (mROS) and an increase in caspase-3 activity are established mechanisms that lead to skeletal muscle atrophy via the upregulation of protein degradation pathways. However, the mechanisms upstream of an increase in mROS and caspase-3 activity in conditions of muscle atrophy have not been identified. Based upon knowledge that an event known as mitochondrial permeability transition (MPT) causes an increase in mROS emission and the activation of caspase-3 via mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…This is consistent with a previous study where they also reported a significantly higher level of SIRT3 and SOD2 in the skeletal muscle of master athletes (~15 years younger than studied here) compared to age-matched controls ( Koltai et al, 2018 ). Finally, mitochondrial permeability transition is an important source of elevated mitochondrial ROS in skeletal muscle ( Burke et al, 2021 ) and SIRT3, which was elevated in MA, reduces mitochondrial permeability transition by deacetylation of cyclophilin D ( Hafner et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a previous study where they also reported a significantly higher level of SIRT3 and SOD2 in the skeletal muscle of master athletes (~15 years younger than studied here) compared to age-matched controls ( Koltai et al, 2018 ). Finally, mitochondrial permeability transition is an important source of elevated mitochondrial ROS in skeletal muscle ( Burke et al, 2021 ) and SIRT3, which was elevated in MA, reduces mitochondrial permeability transition by deacetylation of cyclophilin D ( Hafner et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sporadic denervation in mouse muscle has been shown to reduce mitochondrial respiratory capacity and increase sensitivity to mPTP opening [ 172 ]. Furthermore, mitochondrial permeability shift has been identified as a new pathogenesis of skeletal muscle atrophy, which acts through mitochondrial ROS emission and Caspase-3 activation [ 173 ]. It is worth noting that the mPTP activation is associated with mitochondrial Ca 2+ homeostasis and mitochondrial ROS, which together influence mitochondrial function.…”
Section: Role Of Mitochondria In Muscle Atrophymentioning
confidence: 99%
“…It has been demonstrated that mPTP induction activates caspase‐3 activity in myofiber atrophy. 28 Caspase‐3 activity was blocked in liver‐specific CypD knockout mice in the I/R model, as indicated by cleaved caspase‐3 expression. Therefore, CypD may contribute to hepatocyte apoptosis in a caspase‐3‐dependent manner in liver I/R injury.…”
Section: Discussionmentioning
confidence: 98%
“…The activation and function of caspases, which are involved in the delicate caspase–cascade system, is vital in the process of apoptotic signal conduction. It has been demonstrated that mPTP induction activates caspase‐3 activity in myofiber atrophy 28 . Caspase‐3 activity was blocked in liver‐specific CypD knockout mice in the I/R model, as indicated by cleaved caspase‐3 expression.…”
Section: Discussionmentioning
confidence: 99%